The Effectiveness of the AYU-OCS Portal in Improving Teachers’ Teaching Activities in The Classroom - Hamidah Mat; Farrah Wahilda Khirluddin; Nurlisa Kamba; Wan Hazaruddin Wan Hassan; Muhammad Suffi Yusof; Zuly Rahimie Zulkfli; Lim Yiet Im; Agila Themmedu (Malaysia Journal of Invention and Innovation, 2025)
This study evaluates the AYU-OSC Portal, a digital education platform designed to enhance teaching practices and student engagement. Leveraging a quantitative approach, data were collected from 135 educators, predominantly female (85.9%), aged 35–54 years (88.2%), with most holding bachelor’s degrees (69.6%) and having 10–20 years of teaching experience (63.7%). The portal demonstrated high usability, with mean scores of 4.45 (SD = 0.70) for ease of use and 4.30 (SD = 0.81) for frequent usage. Accessibility ratings were also strong, particularly in enhancing self-education (Mean = 4.59, SD = 0.55) and adaptability (Mean = 4.56, SD = 0.53). Aligned closely with curriculum needs, the portal's resources scored highly for their effectiveness, with mean scores of 4.53 for both alignment and multimedia engagement. Teachers highlighted its positive impact on knowledge exchange, self-directed learning, and overall classroom dynamics. However, some challenges were noted, including navigation complexity (Mean = 3.53, SD = 1.16), suggesting areas for refinement. To further optimize the portal, respondents recommended integrating interactive elements, gamification, and advanced content to cater to higher education needs. These enhancements would elevate engagement levels and address diverse user preferences. The AYU-OSC Portal stands out as a scalable and inclusive solution, leveraging digital tools to meet modern educational demands. By addressing user feedback and refining its features, the platform demonstrates significant potential to transform teaching methodologies, foster equitable learning opportunities, and support educational innovation on a broader scale.